Association of women’s empowerment with childhood immunisation coverage in South and Southeast Asia: meta-analysis of Demographic and Health Surveys data from 11 countries - Quanbao Jiang; Muhammad Usman Saleem; Abdul Ghani Khatir; Tingshuai Ge; Tolulope Ariyo; Negina Rahman (BMJ Global Health)
Background Child health and gender inequalities are significant global public health issues that demand immediate action, particularly in South and Southeast Asian (SSEA) countries where both challenges are prevalent. This study examines the association between women’s empowerment and child vaccination coverage in 11 SSEA low- and middle-income countries.Methods Using population-level cross-sectional data from Demographic and Health Surveys across 11 SSEA countries, we developed an Individual-Level Women’s Empowerment Index (ILWEI) based on three dimensions of women’s empowerment: decision-making autonomy, attitude towards intimate partner violence and social independence. A three-stage mixed-effect individual participant data meta-analysis was employed to assess the association between ILWEI and childhood immunisation coverage.Results In India, 81.28% of women reported participation in three to four decision-making areas, followed by 62.07% in Bangladesh. Full immunisation coverage ranged from 32.43% in Afghanistan to 63.30% in Bangladesh. The association between women’s empowerment and vaccination coverage varied across South and Southeast Asia, with the strongest positive associations observed in Pakistan. However, mixed or negative associations were found in countries such as India and Timor-Leste.Conclusion Our findings indicate that in several SSEA countries, including Pakistan, Cambodia, the Philippines and Afghanistan, higher levels of individual women’s empowerment are positively associated with an increased likelihood of childhood immunisation coverage. However, in countries such as India, Myanmar and Timor-Leste, higher women’s empowerment was associated with lower odds of childhood immunisation, highlighting potential contextual or systemic barriers that may hinder vaccination uptake. This underscores the critical role of women’s empowerment in enhancing childhood vaccination intake while also emphasising the need for targeted interventions to address country-specific challenges. Coordinated, multifaceted strategies are essential to empower women and thereby support the immunisation of children across regions.